Visualization of microbes by 16S in situ hybridization in term and preterm placentas without intraamniotic infection - Seferovic, Maxim D.; Pace, Ryan M.; Carroll, Matthew; Belfort, Benjamin; Major, Angela M.; Chu, Derrick M.; Racusin, Diana A.; Castro, Eumenia C.C.; Muldrew, Kenneth L.; Versalovic, James; Aagaard, Kjersti M. (American journal of obstetrics and gynecology, 2019)
Numerous reports have documented bacteria in the placental membranes and basal plate decidua in the absence of immunopathology using histologic techniques. Similarly, independent metagenomic characterizations have identified an altered taxonomic makeup in association with spontaneous preterm birth. Here we sought to corroborate these findings by localizing presumptive intact bacteria using molecular histology within the placental microanatomy. Here we examined for microbes in term and preterm gestations using a signal-amplified 16S universal in situ hybridization probe set for bacterial rRNA, alongside traditional histologic methods of Warthin–Starry and Gram stains, as well as clinical culture methodologies. We further sought to differentiate accompanying 16S gene sequencing taxonomic profiles from germ-free (gnotobiotic) mouse and extraction and amplicon contamination controls. Placentas were collected from a total of 53 subjects, composed of term labored (n = 4) and unlabored cesarean deliveries (n = 22) and preterm vaginal (n = 18) and cesarean deliveries (n = 8); a placenta from a single subject with clinical and histologic evident choriomanionitis was employed as a positive control (n = 1). The preterm cohort included spontaneous preterm birth with (n = 6) and without (n = 10) preterm premature rupture of membranes, as well as medically indicated preterm births (n = 10). Placental microbes were visualized using an in situ hybridization probe set designed against highly conserved regions of the bacterial 16S ribosome, which produces an amplified stable signal using branched DNA probes. Extracted bacterial nucleic acids from these same samples were subjected to 16S rRNA metagenomic sequencing (Illumina, V4) for course taxonomic analysis, alongside environmental and kit contaminant controls. A subset of unlabored, cesarean-delivered term pregnancies were also assessed with clinical culture for readily cultivatable pathogenic microbes. Molecular in situ hybridization of bacterial rRNA enabled visualization and localization of low-abundance microbes after systematic high-power scanning. Despite the absence of clinical or histologic chorioamnionitis in 52 of 53 subjects, instances of 16S rRNA signal were confidently observed in 13 of 16 spontaneous preterm birth placentas, which was not significantly different from term unlabored cesarean specimens (18 of 22; P > .05). 16S rRNA signal was largely localized to the villous parenchyma and/or syncytiotrophoblast, and less commonly the chorion and the maternal intervillous space. In all term and unlabored cesarean deliveries, visualization of evident placental microbes by in situ hybridization occurred in the absence of clinical or histologic detection using conventional clinical cultivation, hematoxylin–eosin, and Gram staining. In 1 subject, appreciable villous bacteria localized to an infarction, where 16S microbial detection was confirmed by Warthin–Starry stain. In all instances, parallel sample principle coordinate analysis using Bray-Cutis distances of 16S rRNA gene sequencing data demonstrated consistent taxonomic distinction from all negative or potential contamination controls (P = .024, PERMANOVA). Classification from contaminant filtered data identified a distinct taxonomic makeup among term and preterm cohorts when compared with contaminant controls (false discovery rate <0.05). Presumptively intact placental microbes are visualized as low-abundance, low-biomass and sparse populations within the placenta regardless of gestational age and mode of delivery. Their taxonomic makeup is distinct from contamination controls. These findings further support several previously published findings, including our own, which have used metagenomics to characterize low-abundance and low-biomass microbial communities in the placenta.